Granice społecznej tolerancji - Oleksiuk, Inga (My University, 2005)
The Internet, a network covering the majority of the world, changes the way we create and exchange information. What is its potential to change the way people interact and express themselves? New media enable those with a particular interest to communicate with each other instantly, whatever the vehicle may be: chat lines, news groups, replies through email, or even browsing on each other’s web sites. Individuals interested in very specific and obscure research can interact with people focusing on the same subject in another part of the world in no time. This provokes fast changes of sociopolitical notions and a greater variety of human endeavors. Can this be regarded as a benefit to mankind? The author discusses the potential of new media to transgress the traditional boundaries. What are the values that will need to be re-evaluated? Are we closer to a multicultural dialogue or rather to intercultural conflicts? Tolerance and censorship seem to be at the center of the controversy.
The Limits of Social Tolerance